Islamic Boarding School-Based Education in Challenging Ethnic Stereotypes and Social Resistance: Lessons from a Multicultural Community in Indonesia - Murdianto (International Journal of Social Sciences and Humanities, 2026)
This study aims to analyze the role of Islamic education based on pesantren in challenging ethnic stereotypes and reducing social resistance in multicultural societies in Indonesia. Pesantren has so far not only functioned as a religious education institution, but also as a social space that brings together students from various ethnic, linguistic, cultural, and social class backgrounds. In the context of increasing identity polarization, social prejudice, and societal fragmentation, pesantren have strategic potential in building social cohesion through the values of ukhuwah, tolerance, deliberation, and respect for diversity. This study uses a qualitative approach with a multi-site study design in several multicultural Islamic boarding schools in Indonesia. Data was obtained through in-depth interviews, participatory observations, documentation, and targeted group discussions with caregivers, teachers, students, alumni, and the surrounding community. Data analysis is carried out through data reduction, theme categorization, source triangulation, and critical interpretation. The results of the study showed that pesantren education practices were able to deconstruct ethnic stereotypes through collective life in dormitories, collaborative learning, shared religious traditions, and inclusive kiai leadership. In addition, social resistance from the surrounding community can be minimized through community service programs, cultural dialogue, and cross-community social networks. This research emphasizes that pesantren is a transformative Islamic education model that is relevant in strengthening national integration and caring for Indonesia's diversity. The implications of this study encourage the strengthening of a multicultural curriculum based on moderate Islamic values in religious education institutions.